Low temperature influence on long channel STI last process relaxed and strained Ge pFinFETs - Oliveira, A. V.; Agopian, P. G.D. [UNESP]; Martino, J. A.; Simoen, E.; Mitard, J.; Witters, L.; Collaert, N.; Claeys, C. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
The operation of germanium p-type channel FinFETs with two types of different channels, namely, relaxed and strained, is compared from room temperature down to 77 K. The most interesting finding is a higher ION over IOFF ratio for the strained device, achieving around three orders of magnitude higher value than the relaxed channel at 77 K thanks to the strong hole mobility enhancement and thermal deactivation of the off-state current at low temperature.
Keywords: FinFET; germanium channel; Ion/Ioff ratio; low temperature; relaxed; strained